2019
DOI: 10.5430/wje.v9n1p38
|View full text |Cite
|
Sign up to set email alerts
|

Career Decision Regret as a Predictor: Do Teachers and Administrators Regret Due to Their Career Choice?

Abstract: This research aims to explore the relationship between career decision regret, job satisfaction and life satisfaction aswell as determining whether career decision regret significantly predicts job satisfaction and life satisfaction. Havinga descriptive research design, the research has employed relational survey model. The population of the researchholds a total of 7671 teachers and administrators who work at pre-school education institutions, primary, secondaryand high schools located within the central prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
(27 reference statements)
0
5
0
2
Order By: Relevance
“…Overcoming regrets and reconciling the consequences can be a life‐long tiring process by increasing the occupational burnout of individuals, unless the factors that cause such regrets regarding the choice of profession, which is at the origin of the career path, are taken into account (Dyrbye et al., 2020; Hennessey, 2011; Tian et al., 2019). The study results demonstrated that career regret leads to job dissatisfaction (Köse, 2019), burnout (Doğanülkü & Kırdök, 2021), a tendency to leave work (Santra & Giri, 2017), and an increase in turnover intention (Avşar‐Doğrusöz et al., 2022). As it results in numerous adverse outcomes, it is crucial to understand the complex structure of the career path that may cause regret in order to make healthier decisions and reduce career regret.…”
Section: Introductionmentioning
confidence: 94%
“…Overcoming regrets and reconciling the consequences can be a life‐long tiring process by increasing the occupational burnout of individuals, unless the factors that cause such regrets regarding the choice of profession, which is at the origin of the career path, are taken into account (Dyrbye et al., 2020; Hennessey, 2011; Tian et al., 2019). The study results demonstrated that career regret leads to job dissatisfaction (Köse, 2019), burnout (Doğanülkü & Kırdök, 2021), a tendency to leave work (Santra & Giri, 2017), and an increase in turnover intention (Avşar‐Doğrusöz et al., 2022). As it results in numerous adverse outcomes, it is crucial to understand the complex structure of the career path that may cause regret in order to make healthier decisions and reduce career regret.…”
Section: Introductionmentioning
confidence: 94%
“…Career decision regret is a feeling that arises when individuals compare their current career decisions with alternatives (Galinsky et al, 2005;Zeelenberg & Pieters, 2007). In fact, it is a discomfort with career choice.Studies have shown that career regret affects many important aspects related to the individual's life and career, such as burnout (Doğanülkü & Kırdök, 2021), life satisfaction (Köse, 2019), job satisfaction (Köse, 2019), and tendency to leave work (Santra & Giri, 2017). With the regret experienced as a result of the decision, individuals experience intense unhappiness by thinking that they missed the alternatives (Brehaut et al, 2003).…”
Section: The Moderating Role Of Career Decision Regretmentioning
confidence: 99%
“…Buna göre mevcut araştırma bulgusuyla paralel olarak öğretmenlerin yüksek düzeyde iş doyumuna sahip oldukları bulgusuna ulaşan araştırmaların (Aşlamacı, 2017;Başaran & Güçlü, 2018;İdi, 2017;Kahveci, Kotbaş & Bayram, 2019;Polatkan, 2016;Sevinç & Durmuşçelebi, 2020) sayısı fazladır. Öğretmenlerin iş doyumlarının orta düzeyde olduğu araştırmaların (Can, Can & Dalaman, 2010;Çakmak & Arabacı, 2017;Demirtaş & Nacar, 2018;İnce & Şahin, 2016;Köse, 2019;Yıldız, 2013) sayısı da oldukça fazladır. Bununla birlikte literatürde sayıca az da olsa öğretmenlerin düşük düzeyde iş doyumuna sahip olduğu bulgusuna ulaşan araştırmalara (Şahin, 2013;Crossman & Haris, 2006;Mora & Ferrer-i-Carbonell, 2009) da rastlanmaktadır.…”
Section: Tartışma Ve Sonuçunclassified